A suggested business plan for a small to medium-sized creative company - Sulaiman, Haryaman Justisia (Jurnal Akuntansi dan Manajemen, 2025)
Indonesia is among the countries that have the potential to generate GDP through the creative economy. Bekraf, an institution dedicated to advancing the creative economy in Indonesia, was established by the Indonesian government. However, creative industry actors must still contend with obstacles in the development process, including competitive advantages, market conditions, and the industry's long-term objectives. One of the studio agencies offers products from one of the fastest-growing subsectors among seventeen subsectors, namely visual communication design. The researcher conducted interviews and distributed questionnaires to eleven respondents in this research, which combines quantitative and qualitative methods. In addition to internal and external analysis, the researcher employed importance and performance analysis as consumer analysis. Additionally, the researcher conducted a root cause analysis. The development of alternative strategies through applying SWOT and TOWS matrix analysis. Five alternative business strategies were generated due to the integration of four factors: optimizing digital marketing, developing and innovating, enhancing work processes and marketing mix, becoming a legal company, and participating in government programs. It involves establishing the estimated costs, the individual responsible for the project, and the timeline for the company to execute these strategies. The alternative strategy implemented is anticipated to solve creative industry participants' challenges.